QUANTUM LEARNING: EXPERIMENT TO INCREASE LEARNING OUTCOMES - Puri Wulanditya (Universitas Negeri Malang, 2013)
Â Abstract: Quantum learning is a learning method that considers all aspects required in the learning process. Quantum methods can be used as an alternative model of learning in a complicated course such as statistics. This study uses experimental pretest-posttest control group design involving students major in management as an experiment group and students major in accounting as a control group. This study tests the application of quantum learning to improve student learning outcome at statistical course. The result of this study indicates that quantum learning improve student learning outcome. However the gain scores are not much different between the group that was treated and untreated. Quantum learning can be used as an alternative method of learning, because by applying quantum learning, more students gain their confidence and increase their motivation. Abstrak: Quantum learning merupakan suatu metode pembelajaran yang mempertimbangkan semua aspek yang dibutuhkan dalam proses pembelajaran. Metode quantum dapat digunakan sebagai alternatif model pembelajaran dalam matakuliah yang rumit seperti statistik. Penelitian ini menggunakan desain eksperimen pretest-posttest control group melibatkan mahasiswa manajemen dan mahasiswa akuntansi. Penelitian ini menguji apakah penerapan pembelajaran quantum dapat meningkatkan hasil belajar siswa pada mata kuliah statistika. Hasil penelitian ini menunjukkan bahwa pembelajaran quantum dapat meningkatkan hasil belajar mahasiswa. Meski demikian, hasil gain score antara kelompok yang diberi perlakuan dengan yang tidak diberi perlakuan tidak jauh berbeda. Quantum learning dapat digunakan sebagai alternatif metode pembelajaran, karena dengan menerapkan pembelajaran quantum, lebih banyak siswa yang meningkat rasa percaya dirinya serta meningkat motivasinya.